Outward FDI and Its Implication on Indonesian Domestic Investment - Tutik Wiryanti Gondo; Tajul Ariffin Masron; Haslindar Ibrahim; Nik Hadiyan Nik Azman (Asian Academy of Management Journal, 2021)
Since becoming a democratic country in the late 1990s, Indonesia has been changing into a more promising countries with a remarkable reduction in poverty by more than 50% during the last decade. To achieve a developed or high-income country, Indonesia must grow by 8% to 9% annually with huge investment is needed in every sector, ranging from infrastructure to human development in the digital era. Apart from strengthening tax revenue collection, Indonesian government must also investigate the role of outward foreign direct investment (OFDI) that potentially affects domestic investment in the negative way. Hence, it is the objective of this study to examine the impact of OFDI on Indonesian domestic investment for the period between 1980 and 2018. By applying vector error correction model, we observe that OFDI has significant adverse effect on domestic investment. With current inflows of foreign direct investment (FDI) has also never reached to the level prior to the 1997 economic crisis, discouraging the outflows of FDI could be a desirable strategy.